Species wise incidence of malaria in pediatric age group of Raichur district, India - Patel, Abhishek; K., Srinivasa; G. A., Manjunath (International Journal of Contemporary Pediatrics, 2018)
Background: The incidence of malaria is on the raise in Raichur district of Karnataka in the recent years and there is not much studies on malaria from this region. A hospital and community-based study was conducted to know the species wise incidence of malaria in pediatric age group of Raichur district and to know the efficacy of rapid diagnostic test for the diagnosis of malaria, against the gold standard ‘Microscopic examination’ of thick and thin smear. Methods: Blood samples from 676 children with clinical suspicion of malaria were tested by PBS study and RDT. Differentiation of malaria parasite is based on antigenic differences between pLDH isoforms. Results from the RDT were compared to those obtained by PBS. Results: A total of 302 (44.67%) samples were positive by PBS method of which 54 (8.0%) are Plasmodium falciparum, 248 (36.9%) are Plasmodium vivax and, while 218 (32.2%) were positive by RDT 37 (5.5%) Plasmodium falciparum, 181 (26.8%) Plasmodium vivax. In present study the overall incidence of Plasmodium vivax in Raichur district is 36.69% and Plasmodium falciparum incidence is 7.99% and none of the samples have tested positive for Plasmodium malariae and Plasmodium ovale species among the study group. The RDT showed sensitivities of 53.70% and 66.13% and specificities of 98.71% and 96.03%, respectively for the detection of Plasmodium falciparum and Plasmodium vivax. Conclusions: Plasmodium vivax species remains the most common malarial parasite among the positive case by PBS method in Raichur district, but the incidence of plasmodium falciparum is on the rise which is a matter of concern. The RDT method has a low sensitivity and specificity for the diagnosis of malaria since the identification of the four-parasite species is not possible. The careful examination of a well-prepared and well-stained blood film currently remains the "gold standard" for malaria diagnosis.